Gestão de satisfação e fidelidade do cliente: um estudo com turistas em hotéis - Carlos, Francisco de Assis (2014)
This Thesis deals with a study on customer satisfaction and loyalty focusing on a model of factors antecedents of customer satisfaction and loyalty. The model is based on a Satisfaction Index model adopted in Norway developed by Johnson et al.(2001) and the service quality drivers from the literature. It is surveyed a sample of tourist in Natal. It is used a survey questionnaire applied at the airport in the departure moment of the tourist. The final sample results on 198 cases. Is is used a multiple regression analysis as the method to verify the factor affecting satisfaction and loyalty. Two models arise from the analysis. The first model concerning satisfaction results with cleaness and hygiene of the bathroom, leisure facilities, employees promptness, and price as the significant factors affecting satisfaction. The model has a R2 of 0.6430 and the also check in service, cleaness of the apartment and the hotel in general, bedroom setting have colinearity with some factors entering the model. The loyalty model results with satisfaction, affective commitment as the main factors affecting loyalty, with a R2 0.5396, and also image has collinearity with satisfaction. A small part of the sample has complained and this factor was not considered in the models. The results are consistent with the literature in term of quality as the main driver of the satisfaction and that it is not the only one factor to explain loyalty